(untitled) (Journal of Contemporary Philology, 2025)
The phenomenon of Differential Place Marking (Haspelmath 2019), also called zero-marking of spatial relations (Stolz et al 2014), has often been mentioned in the languages of the Balkans. Examples of such differential marking have been documented in the Aromanian varieties (Kramer 1981; Caragiu-Marioțeanu 1975), Modern Greek (Holton et al 1997), Macedonian (Koneski 1965), Ancient Greek (Luraghi 2017), and Latin (Haspelmath 2019; Kramer 1981). However, while the presence of Differential Place Marking has been widely acknowledged, detailed descriptions of such patterns in different varieties are still lacking. Our aim is to present and discuss linguistic data from Aromanian and other Balkan Romance varieties (Istroromanian and Meglen Vlach) to better understand the inter- and intra-dialectal variation of Differential Place Marking. We study and compare their occurrences in the linguistic transcripts from different synchronic Aromanian varieties: from Kruševo (Gołąb 1984), Ohrid and Struga (Markoviḱ 2007), and Turia/Kranéa (Bara et al 2005). The results of the comparative analysis suggest that the dialectal and diachronic picture is not uniform. Various semantic factors, such as the type of noun indicating location (proper vs. common) and whether the location is perceived as proximal or distant seem to play a key role.